(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Abstract Financial literacy is a key factor in determining an individual's financial stability and instability. For their future, youth need to have a solid understanding of financial matters. In the context of a developing economy like India, where social safety benefits beyond retirement are non-existent in contrast to many advanced nations, this is of the utmost importance. Additionally, due to the development of complex economic items, boys and girls must develop their ability to make economic decisions. Because of this, a student must be financially literate in order to make wise financial decisions. Financial awareness can be developed through teachers, classmates, friends from school, and parents at home. Financial awareness can be developed through teachers, classmates, friends from school, and parents at home. In the present study, students, teachers, and parents were interrogated to gather their viewpoint on financial awareness. A questionnaire was used to gather primary data from 95 parents, 90 teachers and 418 high school students from Pune, Maharashtra. It was shown that students are keen to develop their financial literacy. It was also discovered that parents and teachers play a role in shaping pupils' financial attitudes. It was discovered that administering a quiz and playing various financial activities significantly influenced school students' financial attitudes.